Asesmen Augmented Reality dengan SEM terhadap Furindo Apps melalui TAM guna Pemanfaatan Interkonektivitas Teknologi Pasca-Pandemi - Nugraha, Billy; Hasbullah, Hasbullah; Pauji, Ipan (Universitas Suryakancana, 2025)
Today's technology and information are very significant in its development, one of which is e-commerce which is available in several applications. In addition, there is one e-commerce application that has just emerged and is available to its users, namely Furnitur Indonesia Applications (Furindo Apps). Since Furindo Apps is a new application used by users, it is not yet certain about its suitability for users. So the purpose of this study will be to assess several variables that are adjusted to the results of previous research. In this study, one of the methods for assessing augmented reality with the Structural Equation Model (SEM) on Indonesian Furniture Applications through the Technology Acceptance Model (TAM) will be used. Apart from that, in supporting the use of post-pandemic technology interconnectivity. The results in the study focused on several variables used in the hypothesis such as: Quality of Information (X1), Interactive (X2), Perceived Usefulness (X3), Perceived Ease of Use (X4), Enjoyment (X5), Behavioral Intention (X6), Attitude (X7), and Satisfaction (X8). So each variable will be known whether or not there is an influence given by simple statistical testing, namely through a correlation test. The conclusion in this study is that it is necessary to add other variables to support the results of a more optimal TAM method. Teknologi dan informasi masa kini sangat signifikan dalam perkembangannya, salah satunya adalah e-commerce yang tersedia di beberapa aplikasi. Selain itu terdapat salah satu aplikasi e-commerce yang baru muncul dan tersedia oleh penggunanya, yaitu Furnitur Indonesia Applications (Furindo Apps). Berhubung Furindo Apps merupakan aplikasi baru yang digunakan oleh pengguna, maka belum dapat dipastikan perihal kesesuaian dengan penggunanya. Sehingga tujuan dalam penelitian kali ini akan melakukan penilaian terhadap beberapa variabel yang disesuaikan dengan hasil penelitian terdahulu. Pada penelitian kali ini akan menggunakan salah satu metode guna asesmen augmented reality dengan Structural Equation Model (SEM) terhadap Furnitur Indonesia Applications melalui Technology Acceptance Model (TAM). Selain dari itu dalam menunjang pemanfaatan interkonektivitas teknologi pasca-pandemi. Hasil dalam penelitian berfokus pada beberapa variabel yang dijadikan dalam hipotesis seperti: Quality of Information (X1), Interactive (X2), Perceived Usefulness (X3), Perceived Ease of Use (X4), Enjoyment (X5), Behavioral Intention (X6), Attitude (X7), dan Satisfaction (X8). Maka masing-masing variabel akan diketahui ada tidaknya pengaruh yang diberikan dengan pengujian statistik sederhana, yaitu melalui uji korelasi. Kesimpulan dalam penelitian ini perlu dilakukan penambahan variabel lainnya guna mendukung hasil dari metode TAM yang lebih optimal.